Traditional Charm in Luxury: Cathedral Train Dress With Gajah Oling Batik - Romadhona Chusna Tsani; Indriani Oktavia (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The Cathredral Train dress is a formal dress that has a long tail on the back of the dress. This dress has a luxurious and magnificent impression and is commonly used for important occasions such as weddings and other formal events. Cathredral Train dress tends to use plain luxury fabrics without patterns with elegant sequin embellishments. The innovation of the Cathredral Train dress using traditional fabrics has become a new inspiration for fashion enthusiasts. Combining the traditional concept of batik with a luxurious modern fashion style, reflecting the fusion of culture and contemporary fashion trends. Gajah Oling batik is a typical Banyuwangi batik that is commonly used by the surrounding community in traditional ceremonies that are sacred. Gajah Oling batik is believed by the community to be a symbol of prosperity. The formal philosophy of Gajah Oling Batik is in accordance with the characteristics of the Cathredral Train Dress which is used on formal or ceremonial occasions. The combination of dress with traditional Batik of Gajah Oling will produce novelty in the Cathredral Train dress that already exist today. The method used is a qualitative method with descriptive data analysis. This research resulted in a combination of luxury dress with a combination of traditional Gajah Oling Batik.